Extraction of Some Bioactive Phytochemical Constituents from Flaxseed (Linum usitatissimum L.) Oil by Gas Chromatography-mass Spectrometry (GC-MS) and Atomic Absorption Method - Rasha Khalid Abbas (Recent Developments in Chemistry and Biochemistry Research Vol. 5, 2024)
The present study aimed to determine the extraction of some bioactive phytochemical constituents from flaxseed by Gas Chromatography-mass Spectrometry (GC-MS) and Atomic Absorption method. Flaxseed (Linum usitatissimum L.) is an important source of oil. The dried seed of flaxseed 100 g, produced 38% of oil extracted by n-hexane, the physiochemical properties of flaxseed such as acid value (0.71 mg KOH/g) as oleic acid, peroxide value (2.69 meq O2/kg), saponification value (186.50 mg KOH/g oil), and iodine value (96.67 g/100 g), density (0.91 g/cm3), refractive index (1.39 and at 28°C), viscosity (CST) (68.33). Flaxseed oil is the richest plant source of oleic, linoleic (omega-6), and linolenic (omega-3) polyunsaturated fatty acids (PUFA), which are essential for humans. Gas Chromatography-Mass Spectrometry (GC-MS) was used to identify bioactive phytochemical constituents in flaxseed. 26 compounds were identified, the major compounds were 9-Octadecenoic acid (Z), (Oleic acid) (43.72) act as antioxidants, anti-cancer, Hexadecanoic acid, (Palmitic acid) (17.36) act as anti-oxidant, decrease blood cholesterol, anti-inflammatory, 9,12,15-Octadecatrienoic acid, (Z,Z,Z) fatty acids:\(α\)-Linolenic acid, an omega-3 (n-3) fatty acid \(γ\)-Linolenic acid, an omega-6 (n-6) fatty acid (15.72); Octadecanoic acid Methyl stearate (13.13) used as a food additive, soaps, cosmetics, detergents lubricants, softening and release agents;13-Docosenoic acid, methyl ester, (Z)-(1.31); and cis-11-Eicosenoic acid, methyl ester (0.96) act as antibacterial, antitumor, antifungal, and cytotoxic agents. Atomic absorption is used to identify mineral content. It contains Calcium 1180ppm, Copper 4.1ppm, Ferric 15.7ppm, Zinc 34.58ppm. It is concluded that Flaxseed (Linum usitatissimum L.) is beneficial in the chemical composition used as food oil and contains bioactive compounds with antimicrobial, antiradical, antioxidant, and anticancer properties.